Elevated Lead Exposure in Passive Smokers Among Landfill Workers: Peningkatan Paparan Timbal pada Perokok Pasif di Kalangan Pekerja TPA - Serly Ayu Anggraeni; Puspitasari Puspitasari (Academia Open, 2023)
Background: Air pollution from heavy metals like lead (Pb) and cadmium (Cd) poses health risks, especially for landfill workers. Knowledge Gap: Few studies have compared Pb and Cd levels in janitors who are active and passive smokers. Aims: This study assesses urine Pb and Cd levels in 20 landfill janitors, distinguishing between active and passive smokers. Methods: Urine samples were analyzed using Atomic Absorption Spectrophotometry (AAS), and metal levels were compared by smoking status. Results: Pb levels were below the safety threshold (0.15 mg/L), but passive smokers had higher levels than active smokers. Cd levels were low and unrelated to smoking type. Novelty: The study reveals increased Pb exposure for passive smokers. Implications: These findings suggest the need for stronger health policies to protect landfill workers from passive smoke exposure. Highlights: Increased Risk for Passive Smokers: Passive smokers in landfills showed higher Pb levels than active smokers. Low Cd Levels: Cadmium levels were generally low and unrelated to smoking type. Policy Need: Findings support the need for enhanced health policies to protect landfill workers. Keywords: Heavy Metals, Lead (Pb), Cadmium (Cd), Occupational Health, Passive Smoking